2015
DOI: 10.1117/12.2081169
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and drawbacks of Thiol-ene based resins for 3D-printing

Abstract: The technology of 3D printing is conquering the world and awakens the interest of many users in the most varying of applications. New formulation approaches for photo-sensitive thiol-ene resins in combination with various printing technologies, like stereolithography (SLA), projection based printing/digital light processing (DLP) or two-photon polymerization (TPP) are presented. Thiol-ene polymerizations are known for its fast and quantitative reaction and to form highly homogeneous polymer networks. As the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Using an SLA instrument with a 266 nm laser, thiol-vinyl ether resins without photoinitiator were selectively structured with feature sizes below 50 μm. 149 …”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…Using an SLA instrument with a 266 nm laser, thiol-vinyl ether resins without photoinitiator were selectively structured with feature sizes below 50 μm. 149 …”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…Moreover, fast polymerization rate of thiol–ene systems can increase the printing speed and decrease amount of photoinitiator , which reduces the cost and prevents the resin from yellowing. Thiol–ene binary systems have been applied to DLP 3D printing to fabricate objects with high resolution . Recently, our group reported a series of 3D printable thiol–ene systems with high stability.…”
Section: Introductionmentioning
confidence: 99%
“…[30,[33][34][35][36] In this application, thiol-ene addition also provides highly advantageous spatiotemporal control through formation of crosslinked networks only at the times and locations of direct UV exposure. [34,37] For example, a recent report from Sirrine et al described simultaneous chain extension and crosslinking via thiol-ene coupling and acrylamide free radical homopolymerization, which enabled a relatively low viscosity photopolymer to provide properties of higher molecular weight precursors upon photocuring. [34] In another report, Wallin et al demonstrated VP of poly(mercaptopropylmethylsiloxane-codimethylsiloxane) and α,ω-divinyl PDMS, resulting in products with strains at break over 400% and actuatable printed objects.…”
Section: Introductionmentioning
confidence: 99%